Unleashing the potential : transforming technical and vocational education and training - Marope, P.T.M. [Verfasser]; Chakroun, Bohréne [Verfasser]; Holmes, K.P. [Verfasser] (Unesco, 2015)
"In view of steadily rising expectations on technical and vocational education and training (TVET) systems this book takes stock of contextual demands and recent policy trends from around the world. The book identifies an expanding disconnect between the external demands of economic growth, social equity and the sustainability of development and the skills being supplied. The authors ask: 'What would it take to unleash the potential of TVET systems?'. In response an integrated analytical approach is proposed through which economic growth, social equity and sustainability perspectives can be strategically combined so as to address contemporary policy concerns such as youth unemployment, gender disparities and climate change. Policy-makers and other stakeholders may use this approach for the analysis and assessment of TVET systems, to identify appropriate strategies and key enablers for their transformation." (Publisher, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; I 2 Regionen; Berufsbildungssystem; Rahmenbedingungen; Berufsbildungspolitik; Wirtschaftswachstum; Bildungschancengleichheit; Nachhaltige Entwicklung